Design and Experimental Study of Double Intermeshing Planetary Gear Transmission - Wang Yanzhong; Zhao Pengkun; Li Yuan; Wang Dapeng; Jia Shuang (Jixie chuandong, 2017)
Based on the traditional planetary gear transmission technology,the double intermeshing planetary gear transmission is researched and analyzed. The double intermeshing planetary gear transmission has the advantages of compact structure,higher power density,few parts,simple installation condition,and high transmission efficiency. The speed relationship of each component and the force of each component are analyzed.According to the characteristics of the double intermeshing planetary gear transmission,the support structure of the plane is designed. Based on the conversion mechanism method,the transmission efficiency and basic meshing efficiency of the transmission are analyzed. The platform of transmission efficiency test is buit. The transmission efficiency is about 91%,and it is verified that the basic meshing efficiency is very high.